2018
DOI: 10.1177/000313481808400952
|View full text |Cite
|
Sign up to set email alerts
|

Resection Rectopexy is Still an Acceptable Operation for Rectal Prolapse

Abstract: The aim of this study was to compare resection rectopexy (RR) with ventral mesh rectopexy (VMR). This institutional review board–approved retrospective study compared patients with rectal prolapse, who underwent RR or VMR from 2009 to 2016. The primary end point was the comparison of complications and prolapse recurrence rates. Seventy-nine RR and 108 VMR patients qualified. Using propensity score matching, the two groups were not significantly different (P = 0.818). There were no differences regarding gender … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Two [ 11 , 12 ] out of the eight selected studies had extractable data on the operating time of the procedures carried out, and our statistical analysis showed that the two methods did not differ significantly (WMD 68.16, 95% CI −30.28 to 166.6). This analysis is shown in Figure 2 .…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…Two [ 11 , 12 ] out of the eight selected studies had extractable data on the operating time of the procedures carried out, and our statistical analysis showed that the two methods did not differ significantly (WMD 68.16, 95% CI −30.28 to 166.6). This analysis is shown in Figure 2 .…”
Section: Resultsmentioning
confidence: 95%
“…The remaining articles were not included because they investigated different research questions to the one of our study, or on the grounds of including non-adult patients, or because the required data were not extractable. Following the full-text analysis, eight studies in total [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ] were eligible for inclusion in the qualitative and quantitative analysis. The selection process of the included articles can be found in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations